Development Of Blueprint Enterprise Architecture In Academic Field Using Zachman Framework - Guntur Guntur; Sutedi Sutedi (International Journal of Computer Technology and Science, 2025)
The Zachman Framework is one of the methods that can be used to design systems in a structured and comprehensive manner. This study aims to apply the Zachman Framework to design the academic system at SMA Al Kautsar Bandar Lampung, resulting in a blueprint that serves as a guide for system development. The research method involves mapping each perspective in the Zachman Framework, namely Planner (scope), Owner (business model), Designer (system model), and Builder (technology implementation). The findings indicate that the Zachman Framework ensures that all essential aspects of the system are considered, resulting in a structured enterprise architecture design that is efficient and meets stakeholder needs. Furthermore, this framework has proven effective in integrating data and synergizing business functions in the academic section, supporting optimal operations. The implications of this study suggest that the Zachman Framework can serve as an alternative solution for designing and developing an organized, directed, and easily implementable academic system, thus improving the efficiency of business processes in educational institutions.